2022
DOI: 10.1002/1878-0261.13206
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence of CDKN2A/B and IFN‐I homozygous deletions correlates with an immunosuppressive phenotype and poor prognosis in lung adenocarcinoma

Abstract: Homozygous deletion (HD) of CDKN2A and CDKN2B (CDKN2A/BHD) is the most frequent copy‐number variation (CNV) in lung adenocarcinoma (LUAD). CDKN2A/BHD has been associated with poor outcomes in LUAD; however, the mechanisms of its prognostic effect remain unknown. We analyzed genome, transcriptome, and clinical data from 517 patients with LUAD from the Cancer Genome Atlas (TCGA) and from 788 primary LUAD tumor and matched control samples from the MSK‐IMPACT clinical cohort. CDKN2A/BHD was present in 19.1% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…Interestingly, consistent with previous reports HMD at CDKN2A/B were associated with shorter OS and RFS in LUAD [ 33 , 34 ]. In this study, association between aUPD at CDKN2A/B region worsened survival was also observed.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, consistent with previous reports HMD at CDKN2A/B were associated with shorter OS and RFS in LUAD [ 33 , 34 ]. In this study, association between aUPD at CDKN2A/B region worsened survival was also observed.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the prevalence of CNV loss in CDKN2A exceeded 20%. CDKN2A was a cuproptosis suppressor gene, and homozygous deletion of CDKN2A was associated with shorter disease-free survival and OS ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, what is less known is the usual loss of type I interferon genes together with CDKN2A losses (37). Interestingly, those CDKN2A associated type I interferon losses have been shown to present altered immune gene signatures in tumors (38). In myeloma cancer cell lines, which are also frequently depending on IL-6 autocrine signaling, it has been shown that the addition of IFNα in the culture media can downregulate the gene and protein expression of IL-6 receptor subunits and therefore directly hamper the positive feedback loops of the pathway (39).…”
Section: Genomic Somatic Copy Number Alterations Correlate With Plasm...mentioning
confidence: 99%